Effect of Tax Audit on Tax Compliance - Anil Tharu (Journal of Corporate Finance Management and Banking System, 2024)
The study's main focus was on how tax audits affected tax compliance in the Banganga Municipality with particular goals in mind. Numerous statistical tools, including the mean, standard deviation, coefficient of variation, coefficient of correlation, and ANOVA test, were used to achieve these goals. There is a significant correlation between desk audit, field audit, back duty audit, registration audit, and tax compliance. It has been discovered that greater levels of desk audit, field audit, back duty audit, and registration audit performance enhance factors related to tax compliance. Factors have been investigated in this paper. Desk, field, back duty, and registration audits were among the independent variables; tax compliance was the dependent variable.